Evolutionary optimisation-based fractional order controller for web transport systems in process industries. (2019) - Haripriya, N.; Kavitha, P.; Srinivasan, Seshadhri; Belikov, Juri
This investigation presents an optimisation-based design of fractional order proportional integral (FO-PI) controller for web transport systems used in paper industries. The objective of the optimisation algorithm is to reduce the integral absolute error of the closed loop web transport systems considering the underlying physical and operating constraints. The resulting optimisation problem is nonlinear, and to compute the controller parameters, evolutionary algorithms - particle swarm optimisation (PSO) and bacterial foraging optimisation (BFO) are used. The performance improvements achieved using FOC is compared with traditional proportional integral derivative controller. Our results show that BFO tuned FOC shows better performance.